Inflammatory and infectious aortic diseases - Deipolyi, Amy R. (Cardiovasc Diagn Ther, 2018)
Aortitis is aortic inflammation, which can be due to inflammatory or infectious diseases. Left undiagnosed, aortitis can lead to aneurysm formation and rupture, in addition to ischemic compromise of major organs. Infectious aortic diseases include mycotic aneurysm and graft infection; the most common inflammatory diseases are Takayasu’s and giant cell arteritis. We review the epidemiology, etiology, presentation and diagnosis, and treatment of these entities.